Snap nation - Tan, Sheryl Weilin (2017)
SNAP NATION presents an analysis on the phenomenon of ephemeral photography within the digital age. The ubiquity of smartphones has influenced the way photographs are captured today; transforming their role from the preservation of memory to an act of capturing fleeting mundane moments of impermanence. However, are they truly ephemeral? A series of data visualization and recorded video clips on 25 Snapchat and Instagram users over a period of three months, presents what is supposedly ephemeral but herein made visible through reconstruction by the artist, to reveal underlying trends and behavioural traits across all users. It is through the artist’s rigour in recapturing what is gone that ultimately provides tangible evidence to better illustrate society’s unnoticed cultural obsession with capturing the everyday. The project features a total of 5056 video clips that were recorded, trimmed to three seconds each for easy viewing, and then categorized into several trends and sub-trends in chronological order. The data analysis concludes that the sharing of inane details on social media has resulted in behavioural imitation amongst users. Despite human variability, the saturation of overtly similar imagery that fades in time reveals a substantial amount of generic photographic content, which lacks distinction, creativity and authenticity. This suggests that ephemeral photography facilitates social modeling and learning in society, which is powerful but equally stunted, yet ironically we all participate in it.